Indústria 4.0: serviço social no sistema previdenciário em tempos da pandemia de COVID-19 - Souza, Edvânia Ângela De [UNESP] (Programa de Pós-Graduação em Serviço Social e Curso de Graduação em Serviço Social da Universidade Federal de Santa Catarina, 2022)
This text discusses the work scenario of social workers (SW) of Brazilian Social Security (BSS) from the pandemic of the new coronavirus, COVID-19. It seeks to highlight how SW responded to the pandemic, in terms of their work and what the main changes occurred in BSS during this period. It uses a semi-structured interview in the form of a focus group with SW of BSS. The fundamental emphasis is on the computerization processes of social security benefits and telework, corresponding to the deepening of neoliberalism and greater weakening of work.

Este texto discute o cenário do trabalho de assistentes sociais (AS) da Previdência Social (PS) no Brasil, a partir da pandemia do novo coronavírus, COVID-19. Busca evidenciar como AS responderam à pandemia, em termos do seu trabalho e quais as principais mudanças ocorridas na PS nesse período. Utiliza-se de uma entrevista semiestruturada na forma de grupo focal com AS da PS. A ênfase fundamental recai sobre os processos de informatização dos benefícios previdenciários e teletrabalho correspondendo ao aprofundamento do neoliberalismo e maior fragilização do trabalho.
Industry 4.0: social work in the social security system in times of the COVID-19 pandemic
Keywords: COVID-19 pandemic; 4th Industrial Revolution (4th IR); Social Services in Brazilian Social Security; Pandemia COVID-19; 4ª Revolução Industrial (4ª RI); Serviço Social na Previdência Social